Strategi Dinas Kebudayaan Provinsi Daerah Khusus Ibukota Jakarta Dalam Melestarikan Budaya Ondel-Ondel - Muhammad Rizky Febriansyah (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
Due to the growth of globalization, the existing local culture is fading. The state must be able to promote Indonesia's national culture in the midst of civilization. The Preservation of Betawi Culture has been regulated in Regional Regulation Number 4 Year 2015, which the implementation of this regional regulation is still considered weak. Ondel-ondel is one of the Betawi cultural icons which is regulated in the Regulation of the Governor of DKI Jakarta Province Number 11 Year 2017 concerning “Betawi Cultural Icons”. However, the fact is that now ondel-ondel which is an icon of Betawi culture, has undergone a shift in meaning, and is used as a medium for busking. The research method that used in this research is a qualitative descriptive method, using an inductive approach. Data collection was carried out by interview, observation, and documentation. The data analysis techniques used were SOAR analysis and Quantitative Strategic Planning Matrix (QSPM). The results of the research and data processing indicate that the preservation of ondel-ondel culture has currently been carried out in accordance with the direction and goals of the Department of Culture, but due to the Covid-19 pandemic, various art events that are designed cannot be done, then there has been a mutual agreement between SKPD and community organizations in controlling buskers who use ondel-ondel as a media. Based on the SOAR analysis, researchers have succeeded in formulating strategies for the preservation of ondel-ondel culture.